Adsorption of nisin on raw montmorillonite - Ibarguren, Carolina (2014)
The aim of the present work was to develop food-grade materials capable of releasing antimicrobial agents. Montmorillonite (Mt), a raw, abundant inexpensive clay mineral approved as a food additive, was used as support material. The immobilized antimicrobial agent was pure nisin (Danisco, UK). A series of antibacterial compounds were prepared, and the antimicrobial activity of the resultant montmorillonite-nisin (MtNis) immobilized systems was determined against Enterococcus faecium C1. The characterization of the antimicrobial powders showed evidences of nisin adsorption on by means of a "frustrated intercalation" model with a nisin loading (NL) saturation value close to 0.24. CEC (cation exchange capacity) of Mt. The antibacterial powders with NL above this value completely inhibited E. faecium C1 during 24. h of contact. These results are encouraging for the development of nisin-based bioprotectors immobilized on raw Mt.